Have passion and have goals in life - Heziwan - Nurizzatul Alin, Ahmad Bastani (2018)
Universiti Malaysia Pahang (UMP) alumnus Heziwan Hamsah, 32, did not at all fancy being an engineer when he was small but eventually, the profession became his livelihood because of his deep concern over the environment.